Performance evaluation of multi-user detection in Cdma using micro-genetic algorithm - Ahmad, Azmi; Ali, Borhanuddin M.; Khatun, Sabira; Hassan, Azmi (IEEE, 2005)
Two main problem of multi-user communication system are the Multiple Access Interference (MAI) and the near-far effects. While near-far effect problem can be approach by applying power control, the MAI problem requires individual receiver to identify desired signal from interferences thus making multi-user detector a popular area of research. Genetic Algorithms (GA) is a search and optimizes technique that works by estimating multiple solutions in order to come with the best estimated solution. GA works iteratively over a population of solution using crossover and mutation to simulate potential solution. In this paper we examine the performance of a micro-Genetic Algorithm-based multi-user detector. Our simulation shows that μGA achieves a performance close to optimal detector.